Integrated system of public spaces for the proposal of new centralities in the district of Coronel Gregorio Albarracín - Vargas Rodríguez, Jesús Fernando (2016)
Objective: Among the factors aﬀecting the joint within the district Lanchipa Gregorio Albarracı́n and the city of Tacna, as main factor is the lack of centrality. In that sense this research aims to formulate proposals for urban centers through an integrated public spaces in the district of Colonel Gregorio Albarracin Lanchipa system. Method: This research has two phases, the first question according to the type of research: explorative- Explanatory, of a substantial nature. Culminating in a stage of applicative, Social Interest with respect to impact results obtained in the research process. Results: This research led to the Integrated System, the new centers Urban, and the necessary justification to understand all the positive that the correct urban development through systemic factors axes; will be necessary to address each of these centers as an independent, thus further increasing the level of complexity and emergence of new public spaces, character and vocation of use. Conclusions: According to the Concerted Development Plan District Colonel Gregorio Albarracin, and the cadastral plan of land use thereof, this has an estimated 735 land for public spaces, and only 34% have been built to date, 27% of them are under appropriate conditions fulfilling minimum standards of quality space. Therefore the development of an Integrated System for Public Spaces allow the proposal of new urban centers in the Coronel Gregorio Albarracı́n Lanchipa District.